Existence of Fixed Points in Neutrosophic Bipolar Fuzzy Metric Spaces with Application - Gupta, Vishal; Anju, Anju; Thakur, Deepti; Sehgal, Ishit (Journal of the Indonesian Mathematical Society, 2025)
In this paper, we aim to introduce and explain the concept of neutrosophic fuzzy bipolar metric spaces and provide some fixed point results in this new setting. Additionally, we give a detailed presentation of the proof of fixed point theorems using covariant maps, showing how our findings extend and generalize those established in the existing body of literature. The derived results are supported with a suitable example and an application.